Quantum memory at an eigenstate phase transition in a weakly chaotic model - Lambert, M. R.; Tsai, Shan-Wen; Kelly, Shane P. (Physical Review A, 2022)
We study a fully connected quantum spin model resonantly coupled to a small environment of noninteracting spins, and investigate how initial state properties are remembered at long times. We find memory of initial state properties, in addition to the total energy, that are not conserved by the dynamics. This memory occurs in the middle of the spectrum where an eigenstate quantum phase transition (ESQPT) occurs as a function of energy. The memory effect at that energy in the spectrum is robust to system-environment coupling until the coupling changes the energy of the ESQPT. This work demonstrates the effect of ESQPT memory as independent of integrability and suggests a wider generality of this mechanism for preventing thermalization at ESQPTs.
Created from Fastlane, Scopus look-up